Mock trials: A participatory views of the criminal justice process - Starling, Shelby L. (American journal of criminal justice, 1986)
“The whole art of teaching is only the art of awakening the natural curiosity of young minds for the purpose of satisfying it afterwards.” (France, 1881) This quote from The Crime of Sylvester Bonnard, the first novel of the Nobel Prize Winner, Anatole France, emphasizes a primary goal of teaching: awakening and satisfying natural curiosity. While most educators might agree with France’s assessment of educational goals, there seems to be less consensus on how this goal can best be achieved. Just as teachers differ so do teaching strategies. Obviously a variety of strategies can and should be utilized to attain the goal of facilitating learning by students. One of the proven instructional methods which can be utilized is simulation. It offers the opportunity for effective instruction at all levels of education from primary grades through professional schools. In criminal justice education, the use of simulation can provide students with an exciting opportunity to experience “real world” situations in the classrooms. It offers a chance for students to satisfy their natural curiosity through role play. This article describes the development and implementation of a mock trial course at Jacksonville State University.